Prognostic significance of MRI-detected bladder muscle and/or serosal invasion in patients with cervical cancer treated with radiotherapy - Nam, H (The British Institute of Radiology., 2010)
In cervical cancer, the prognostic significance of bladder wall invasion on MRI without pathological evidence of mucosal invasion is not known. From 454 consecutive patients with cervical cancer who were treated with radiation, we reviewed images and analysed the outcome of 92 patients with the Federation of International Gynecology and Obstetrics (FIGO) stage IIIB–IVA. We analysed the patients in three groups, normal, wall (muscle and/or serosal) invasion and mucosal invasion, according to the findings on the MRI. Kaplan–Meier life table analysis and the log-rank test were used to assess the survival rates and differences according to prognostic factors. MRI detected abnormalities in the bladder wall in 42 patients (45.6%): wall invasion in 24 and mucosal invasion in 18. 5 of 18 patients, suspected on MRI to have mucosal invasion, showed no pathological evidence of mucosal invasion. Median follow-up period was 34 months. 3-year cause-specific survival (CSS) in the normal group compared with the wall invasion group was 76.2% vs 71.4% (p = 0.48). 3-year CSS for the wall invasion group compared with the mucosal invasion group was 71.4% vs 54.3% (p = 0.04). Mucosal invasion on MRI (p = 0.03) and concurrent chemoradiotherapy (p = 0.01) was significant for CSS. The prognosis for patients with cervical cancer with evidence of muscle and/or serosal invasion of the bladder on MRI may not differ from that for patients without abnormality on MRI. In patients with the MRI finding of bladder mucosal invasion, further studies should be conducted regarding the role of cystoscopy to determine the need for pathological confirmation.